Jatropha: An Alternative Substitute to Fossil Fuel - Kamrun Nahar; Monica Ozores-Hampton (EDIS)
Jatropha is a tropical plant and can be grown in low to high rainfall and diverse soil types, but the plant is susceptible to freezes. The plant produces seeds containing inedible oil that can be converted to biodiesel. The cake by-product from oil extraction can be used for fish and animal feed, biogas, or as an organic fertilizer. This 10-page fact sheet describes the plant morphology, species adaptability, cultural practices, and crop uses. Written by Kamrun Nahar and Monica Ozores-Hampton, and published by the UF Department of Horticultural Sciences, December 2011. (UF/IFAS Photo by Tyler Jones)